Risk Prison and Hepatitis B Virus Infection among Inmates with History of Drug Injection in Isfahan, Iran - Daneshmand Dana; Nokhodian Zary; Adibi Peyman; Ataei Behrooz (The Scientific World Journal)
Objectives. Hepatitis B virus (HBV) is a health problem among injection drug users (IDUs) in prison. The aim of this study is to evaluate the association of factors of incarceration with HBV infection in prisoners with history of drug injection in Isfahan, Iran. Methods. In a cross-sectional study, all IDUs inmates were enrolled. Sociodemographic characteristics and associated risk factors were obtained. Blood samples were collected and serological markers for HBV were analyzed. For data analysis, odds ratio and logistic regression were used. Results. Of the IDUs inmates, 970 subjects participated in the study. History of imprisonment (OR: 1.82, 95% CI: 1.28–2.57), multiple incarceration (OR: 1.43, 95% CI: 1.01–2.02), and total duration of imprisonment (OR: 2.70, 95% CI: 1.94–3.74) were significantly associated with prevalence of HBV among IDUs inmates. Multivariate analysis of associated factors showed that only total duration of incarceration is significantly associated with HBV infection. Conclusion. In conclusion, according to our results, multiple and duration of incarcerations will be considered as important risk factors of HBV infection in IDUs inmates. This fact makes it important to set some screening and prevention programs in prisons to decrease the risk of being infected and prevent the transmission of these diseases.